2010
DOI: 10.1016/j.annepidem.2010.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Overweight and Obesity in Italy (2001–2008): Is There a Rising Obesity Epidemic?

Abstract: Purpose To provide national, population-based estimates of the prevalence of overweight and obesity in the Italian population. Methods Prevalence estimates of overweight and obesity were calculated in seven waves (2001–2008) of the cross-sectional Multipurpose Household Survey organized by the Italian National Institute of Statistics which are representative of the general adult Italian population. Sampling weights were used to estimate prevalence figures as well as their standard errors. Mean-difference plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 25 publications
3
20
1
Order By: Relevance
“…Importantly, no significant difference in airway inflammation, assessed by FeNO measurement, was found between the two groups of patients. Lastly, as has been reported in the Italian general population [25], we found that an increased BMI becomes more common with increasing age. Incidentally, our results indicate a high rate of obesity among adult asthmatics referred to an Italian tertiary care asthma clinic.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Importantly, no significant difference in airway inflammation, assessed by FeNO measurement, was found between the two groups of patients. Lastly, as has been reported in the Italian general population [25], we found that an increased BMI becomes more common with increasing age. Incidentally, our results indicate a high rate of obesity among adult asthmatics referred to an Italian tertiary care asthma clinic.…”
Section: Discussionsupporting
confidence: 68%
“…As compared to the Italian general population [25], in our cohort of patients we found a higher rate of obese patients. Our data are consistent with the results of a previous Canadian report [4] and suggest that in industrialized countries obesity may be more common among adult tertiary care asthmatics than in the general population.…”
Section: Discussionmentioning
confidence: 55%
“…Despite the important increase in mean BMI recently described in Western Europe (9) , some European countries (37)(38)(39) have reported a slowdown in the rate of increase. The observed increase in these outcome variables could be a herald of a levelling off of the obesity prevalence.…”
Section: Discussionmentioning
confidence: 95%
“…In recent years, the prevalence of overweight and obesity has increased in almost all developed countries. In Italy more than 50% of adult men and about 1 of 3 women are overweight or obese [3]. Obesity and a high body mass index (BMI) have been shown to be risk factors for the development of psoriasis, and in large, prospective studies obesity preceded the development of psoriasis [4].…”
Section: Introductionmentioning
confidence: 99%